2015
DOI: 10.1007/s13204-015-0460-4
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles synthesized by Brassica oleracea (Broccoli) acting as antimicrobial agents against human pathogenic bacteria and fungi

Abstract: Production of antimicrobial agents through the synthesis of gold nanoparticles using green technology has been extensively made consistent by various researchers; yet, this study uses the flower bud's aqueous extracts of Brassica oleracea (Broccoli) as a reducing agent for chloroauric acid (1 mM). After 30 min of incubation, synthesis of gold nanoparticles (AuNps) was observed by a change in extract color from pale yellow to purple color. Synthesis of AuNps was confirmed in UV-visible spectroscopy at the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…It was clear that the current gold nanoparticles in the P. acuminatissimum Radlk leaf extract medium (AuNPs@P. acuminatissimum Radlk leaf extract) represent a potential alternative material for antibacterial action against E. coli. The results also support previous results demonstrating the utility of potential plant extracts for the synthesis of gold nanoparticles and for increasing their activity as antibacterial agents 14,18 .…”
Section: Resultssupporting
confidence: 90%
“…It was clear that the current gold nanoparticles in the P. acuminatissimum Radlk leaf extract medium (AuNPs@P. acuminatissimum Radlk leaf extract) represent a potential alternative material for antibacterial action against E. coli. The results also support previous results demonstrating the utility of potential plant extracts for the synthesis of gold nanoparticles and for increasing their activity as antibacterial agents 14,18 .…”
Section: Resultssupporting
confidence: 90%
“…It is believed that the variation in activity against the bacterial strains is dictated by the nature of the bacterial cell wall. The cell wall of the gram-positive bacterial strains, for example, has a thicker peptidoglycan layer compared to the cell wall of the gram-negative bacteria [ 63 ]. As a result, GNPs can penetrate the cell wall of the gram-negative bacteria and exert their antibacterial action more easily than in gram-positive bacteria [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…3a-d) while the MBC values of 0.14 mM against all the strains except E. coli, against which the MBC value was found 0.12 mM only. Literature survey reveals that there exist a number of reports describing synthesis of AuNPs by plants such as Abelmoschus esculentus (Jayaseelan et al 2013), Euphorbia hirta L. (Annamalai et al 2013), Brassica oleracea (Piruthiviraj et al 2016) that showed effective antimicrobial activity. However, a close study on the reported MIC/MBC values and/or the diameter of zone of inhibition suggests that the antimicrobial activity of our AuNFs is relatively superior compared to some of the reported values (Table 1, Sl No 1-5).…”
Section: Antimicrobial Assaymentioning
confidence: 99%